Grammatical presentation of phrasal verbs in ESL textbooks - Zarifi, Abdolvahed; Mukundan, Jayakaran (Universiti Putra Malaysia Press, 2014)
Despite the notoriously challenging aspects of the English phrasal verbs, these combinations are of high relevance for ESL/EFL learners as knowledge of them is often equated with language fluency and proficiency. They are likely to assume a number of different syntactic patterns, and grammatical presentation of these structures in ESL materials turns out to be a major pedagogical concern. Yet, the body of research dealing with the syntactic representation of these forms is almost missing in the related literature. The present study was, therefore, an attempt to investigate the grammatical treatment of phrasal verbs in Malaysian ESL secondary level textbooks. Although there occured a total number of 15 different syntactic patterns associated with these multiword verbs, they were almost overlooked as a category of language phenomenon enjoying their own grammatical behaviour. There also appeared to be no guiding principle underlying the selection, presentation and sequencing of different patterns associated with them, bringing further home the observation that the development of ELT textbooks is more intuitively than empirically motivated.